KARAKTERISTIK NUTRISI SUSU KERBAU BELANG TORAJA, MAKASSAR - Alang, Hasria; Kusnadi, Joni; Ardyati, Tri; Suharjono, Suharjono (ZOOTEC, 2020)
NUTRITION CHARACTERISTICS OF BUFFALO MILK FROM TORAJA, MAKASSAR. The study was conducted to analyze the nutritional content of milk in Toraja Belang Buffalo. The research method took samples of Toraja Belang buffalo milk in Toraja Regency, South Sulawesi. Sample was put at the cool box before analyzing its nutritional content. The nutrient content of the milk sample was analyzed using a Lacto scan analyzer to see water content, ash content, protein, fat, lactose and BKTL. The results showed that nutritional content of Belang Toraja buffalo milk consisted of protein (3.17%), fat (12.97%), lactose (4.37%), water content (79.49%), ash content (0.88 %) and SNF / BKTL (8.42%).